PENGARUH VOLUNTARY DISCLOSURE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN MANUFAKTUR YANG SAHAM TERDAFTAR DI INDEKS SYARIAH PADA BURSA EFEK INDONESIA - Wahyuddin Albra; Afiza Fadila (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
This research was conducted to analyze the influence of Voluntary disclosure andCorporate social responsibility toward Earnings response coefficient at manufacturingcompanies in Islamic Index of Indonesia Stock Exchange during 2012-2014. Thedata used in this research was secondary data and there were 29 samples taken by applying Purposive sampling technique. The method of data analysis was Multiple linearregression and Classical Assumption test. The result of analysis simultaneouslyindicated that the Voluntary disclosure influenced significantly on Earning responsecoefficient at manufacturing companies in Jakarta Islamic Index with the level ofsignificance about 0.000. Corporate Social Responsibility influenced positively andsignificantly toward Earning response coefficient at manufacturing companies inJakarta Islamic Index with the level of significance about 0,000. Simultaneously,Voluntary disclosure and Corporate social Responsibility influenced positively andsignificantly on the Earning Response Coefficient at manufacturing companies inJakarta Islamic Index.